2015
DOI: 10.1002/app.43091
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell emulsion polymerization of styrene and butyl acrylate in the presence of polymerizable emulsifier

Abstract: A series of core–shell polymeric particles of styrene butyl acrylate were successfully prepared in the presence of polymerizable emulsifier. The compositions of the emulsions obtained were confirmed by Fourier transformed infrared spectrometry. Latexes and emulsion films were characterized by transmission electron microscopy and scanning electron microscopy, respectively. The thermostability of emulsion films was characterized by thermogravimetric analysis. The results showed that the existence of polymerizabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The traditional polyacrylate (PA) printing binder was widely used in pigment printing due to its excellent filmforming ability. 11,12 However, the traditional PA laid emphasis on the adhesion and encapsulation of pigments. 13 PA had a PA in the range 18-23 J 0.5 /cm 1.5 .…”
mentioning
confidence: 99%
“…The traditional polyacrylate (PA) printing binder was widely used in pigment printing due to its excellent filmforming ability. 11,12 However, the traditional PA laid emphasis on the adhesion and encapsulation of pigments. 13 PA had a PA in the range 18-23 J 0.5 /cm 1.5 .…”
mentioning
confidence: 99%
“…One is about 80 nm, and the other is about 40 nm. Besides, TEM micrographs showed that the image of copolymers were spherical core–shell structure, dark color inside, to the outside gently fade, color difference between the two‐phase structures was obvious . The diameter of shell phase was about 40–50 nm, and the core phase was about 30–40 nm.…”
Section: Resultsmentioning
confidence: 98%
“…It is difficult for the free radicals to enter inside of latex particles, which leads to lower conversion. [10] Usually, the mixture of nonionic and anionic surfactant is often adopted in practice. The use of the mixture of nonionic and anionic surfactant can improve the cloud point of nonionic surfactant greatly and make the surfactant molecules be alternately absorbed onto the surface of latex particles, which reduce static repulsion among the ions on the same latex particle and charge density on the surface of latex particles.…”
Section: Resultsmentioning
confidence: 99%